Dynamic performances of adsorbents in an industrial-sized packed bed column for lead ion removal - Bahrun, M.H.V.; Bono, A.; Zaini, M.A.A.; Othman, N.; Saptoro, Agus (SPRINGER HEIDELBERG, 2022)
The dynamic performances of various adsorbents in removing lead ion, Pb(II), from aqueous solution in an industrial-sized packed bed column were investigated through numerical simulation, by employing a linear driving force (LDF) approximation model in Aspen Adsorption simulation tool. The size of the real implemented packed bed column with dimensions of 0.9730 m height and 0.6096 m diameter, with a design flowrate of 631 mL/s and inlet concentration of 0.1 mg/L Pb(II) aqueous solution, was used to represent an industrial-sized packed bed column. Here, the dynamic performances of ten Langmuir-fitted adsorbents for removing Pb(II) from an aqueous solution were evaluated. Among the ten adsorbents, the apricot stone AC gave the highest dynamic adsorptive performance with the highest saturation time (203 days) and percentage removal (95.6%). This suggests a cheaper and environmental-friendly alternative of using biomass-activated adsorbent. Based on the simulation results of the ten adsorbents, a simple analysis method was formulated as a preliminary screening for comparing the adsorptive performance using information from the batch experiments related to separation factor and total adsorbent mass. The Langmuir separation factor, RL, can be used as a preliminary indicator to rank various adsorbents in removing Pb(II). In the case of available adsorbent density, the mtotal indicator is more reliable and gives a better indicator than RL. This present paper provides a preliminary screening in comparing various adsorbents’ performance operated in a packed bed column, especially the industrial-sized packed bed column. Graphical abstract: [Figure not available: see fulltext.]